Demonstration of a gas turbine combustion-tuning method and sensitivity analysis of the combustion-tuning parameters with regard to NOx emissions. (1st March 2019) - Park, Seik; Choi, Gyung Min; Tanahashi, Mamoru
Abstract: Nitrogen oxide (NOx) emission regulations are strengthening to reduce fine particles (particulate matter) in the East Asian, countries including Korea. In this paper, empirical evidence of exhaust gas (NOx) reductions considering the pilot fuel split ratio of a combustion-tuning methodology is provided using the full-scale gas turbine combustion test facility of the KEPCO (Korea Electric Power Cooperation) research institute. The combustion-tuning methodology confirmed in the laboratory was verified by load tests (50%, 70%, and 100% loads) for the Gunsan CCPP (combined cycle power plant) at Korea Western Power. Particularly, empirical tests of the NOx reduction effect of around 20% without the combustion instability phenomenon under a partial load were successfully carried out. The change in the fuel ratio through the tophat and pilot nozzle and the change in the combustion air volume through a bypass valve were analyzed to assess the sensitivity to the amount of NOx emission generated under actual gas turbine (Mitsubishi Hitachi Power System's GT model for power generation: 501G) operating conditions. It was also confirmed qualitatively that the trends of the NOx emission due to a change in the pilot fuel split ratio from full-scale atmospheric test results in a laboratory and actual operation data of the actual gas turbine under a 50% load were similar. Based on the reduced amount of NOx by the combustion-tuning methodology, the basic deductible savings levels for each gas turbine unit due to the exhaust gas regulation were introduced.